The Influence of Scouting Extracurriculares on Interpersonal Intelligence of Primary School Students - Ristiani, Ristiani; Yuliyanto, Aan; Rismawati, Wati; Rini, Rini; Nurlela, Ela; Wulansari, Yuli Sri (International Conference on Elementary Education, 2025)
The ability to communicate, interact, build social relationships, and empathize is known as interpersonal intelligence. This literature review uses an integrative review design to ascertain how scouting extracurricular activities influence the interpersonal intelligence of elementary school students. The attitudes and potential formed in scouting activities are related to several indicators of interpersonal intelligence: empathy, prosocial attitudes, social skills, and communication. This interpersonal intelligence is essential and must be developed, considering the current conditions with various cases of bullying, one of which is caused by the loss of empathy, compassion for others, and poor communication. Of course, this will have an impact on their future and also harm others. The basic principles and methods of scouting educate students to have faith in caring for the nation, others, the environment, and themselves, which can stimulate and develop interpersonal intelligence, one of which is practicing the scout code of honor. The group system in the scouting method provides the opportunity to learn to lead and be led, organize and be organized, take responsibility, and work and cooperate with others. Of course, this activity requires good communication, empathy, prosocial attitudes, and problem-solving skills in groups, which lead to the formation of interpersonal intelligence. This research is based on a literature review by examining several articles and books that are relevant to the research.